AUTHORITY OF BALI PROVINCIAL GOVERNMENT IN THE COLLECTION OF SURFACE WATER TAX IN BALI PROVINCE - Dewa Ayu Sri Susilawati (Jurnal Hukum Prasada, 2018)
Abstract Bali Province as an autonomous region is given authority to conduct all government affairs, which is basically a task of government, development and public service which in its implementation requires financing originating from local taxes. Local Taxes have been submitted to the regions under the guidance of Law Number 28 of 2009 on Regional Tax and Levy. One of the local taxes already managed by the Bali Provincial Government is the Surface Water Tax. The formulations of this research problem is 1) How is the implementation of authority of Bali Provincial Government in Surface Water Tax Collection in Bali Province? 2) How is the implementation of Bali Province Regional Regulation No. 1 of 2011 jo Bali Province Regional Regulation No. 1 of 2015 on Regional Tax?. The Results of this research indicate that: 1) Implementation of authority of Bali Provincial Government in Surface Water Taxation is in accordance with the prevailing laws and regulations, because Law Number 28 of 2009 on Regional Tax and Levy has been followed up with the stipulation of Bali Provincial Regulation Number 1 in 2015, with further elaboration in the Bali Governor's Regulation Number 40 of 2011 on Technical Guidance of Implementation of Provincial Regulation No. 1 of 2011 and Decision of the Head of Bali Province Revenue Service No. 973/5651/DISPENDA on Technical Guidance on the Implementation of Motor Vehicle Tax Collection, Transfer of Motor Vehicle Title, and Surface Water Tax; (2) Implementation of Regional Regulation of Bali Province Number 1 of 2015 Concerning Amendment to Provincial Regulation Bali Number 1 of 2011 Concerning Regional Taxes (especially Surface Water Tax) has not been effective. Keywords: Local Tax Collection, Surface Water Tax,